Effect of multilayer CrN/CrAlN coating on the corrosion and contact resistance behavior of 316L SS bipolar plate for high temperature proton exchange membrane fuel cell. (20th January 2022) - Mani, S. Pugal; Agilan, P.; Kalaiarasan, M.; Ravichandran, K.; Rajendran, N.; Meng, Y.
Highlights: The CrN/CrAlN coating greatly improved the contact angle and corrosion resistance of 316L SS. The CrN/CrAlN coating reduced the ICR and increased the surface conductivity of 316LSS. Single fuel cell test assembled with CrN/CrAlN coating enhanced the performance of HT-PEMFC. Abstract: Stainless steels have received wide attention as a substitute material for bipolar plates in high temperature proton exchange membrane fuel cell (HT-PEMFC). In the present work, the CrN, CrAlN and multilayer CrN/CrAlN coatings were deposited on 316L SS to increase the corrosion resistance and decrease the interfacial contact resistance. The deposited coatings exhibited face centered cubic phase structure and it was verified from the X-ray diffraction pattern. X-ray photo electron spectroscopy results showed the formation of both CrN and CrAlN layers on 316L SS. CrN/CrAlN coating is more helpful in water management due to low surface roughness and high contact angle in the HT-PEMFC environment. The corrosion resistance behavior of all the samples were studied in 85% H3 PO4 solution at 140 °C purged with H2 (HT-PEMFC anode) and O2 (HT-PEMFC cathode) gases. The results showed that all the coatings considerably improved the performance of 316L SS and superior corrosion resistance was observed for CrN/CrAlN multilayer coating, whose protective efficiency was 98.12% and 96.14% in the two simulated HT-PEMFC environments. The results of electrochemical impedance spectroscopic studies demonstrated higher impedance for CrN/CrAlN coating. Surface morphological studies performed after corrosion studies revealed that protection ability of CrN/CrAlN coating still remained acceptable. A very low interfacial contact resistance value of 6 mΩ cm 2 at 140 N/cm 2 was observed for CrN/CrAlN coating. Moreover, after corrosion studies, the interfacial contact resistance value of CrN/CrAlN coated 316L was much lower than that of CrN and CrAlN coatings due to the increased oxidation resistance. The maximum power density of about 0.93 W/cm 2 at 2 A/cm 2 and output voltage of 0.96 V was observed for CrN/CrAlN coating. Graphical abstract: Image, graphical abstract